2013
DOI: 10.1111/cei.12082
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to Streptococcus pneumoniae in asthma patients: comparison between stable situation and exacerbation

Abstract: SummaryIn Argentina, more than 3 million people suffer from asthma, with numbers rising. When asthma patients acquire viral infections which, in turn, trigger the asthmatic response, they may develop subsequent bacterial infections, mainly by Streptococcus (S.) pneumoniae. This encapsulated Gram + bacterium has been considered historically a T cell-independent antigen. Nevertheless, several papers describe the role of T cells in the immune response to S. pneumoniae. We evaluated the response to S. pneumoniae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The expression of lymphocyte activation marker CD69 was increased by Streptococcus pneumoniae antigen. 29 CD69 plays an important role in the pathogenesis of allergen-induced eosinophilic airway inflammation and hyperresponsiveness 30 and inhibits Th17 cell differentiation through activating JAK3-STAT5 pathways. 31 Th17 cells, via IL-17A and IL-17F, promote neutrophil recruitment and have been invoked as a noneosinophilic/non-type 2 pathway in asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of lymphocyte activation marker CD69 was increased by Streptococcus pneumoniae antigen. 29 CD69 plays an important role in the pathogenesis of allergen-induced eosinophilic airway inflammation and hyperresponsiveness 30 and inhibits Th17 cell differentiation through activating JAK3-STAT5 pathways. 31 Th17 cells, via IL-17A and IL-17F, promote neutrophil recruitment and have been invoked as a noneosinophilic/non-type 2 pathway in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pneumoniae has been widely believed to be associated with asthma via immune modulation. The expression of lymphocyte activation marker CD69 was increased by Streptococcus pneumoniae antigen 29 . CD69 plays an important role in the pathogenesis of allergen‐induced eosinophilic airway inflammation and hyperresponsiveness 30 and inhibits Th17 cell differentiation through activating JAK3‐STAT5 pathways 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies also showed impaired CMI after nonspecific stimulation in patients with asthma or atopic dermatitis, but antigen-specific CMI was not impaired. 148,149 We recently assessed CMI responses to the viruses in the measles, mumps, and rubella (MMR) vaccine among children aged 12 to 18 years who had received 2 doses of the MMR vaccine. Asthmatic patients with a family history of asthma had significantly poorer CMI responses to MMR vaccine viruses than did those without asthma.…”
Section: Potential Mechanisms Underlying the Association Between Atopmentioning
confidence: 99%
“…Otero et al (2013) reported that bacterial infection may elicit the imbalanced expression of T helper cells types 1 and 2 (Koch et al, 2007). Peroni et al (2010) analyzed the pathogen distribution in elderly asthmatic patients and revealed that asthma was induced by the ecological imbalance of pathogenic microbes, which was confirmed by an animal experiment study by Piacentini et al (2010).…”
Section: Introductionmentioning
confidence: 84%